Proses Komunikasi Keterbukaan Diri Korban Bullying - Jessica Riantifanny; Wulan Tri Gartanti (UNISBA Press, 2022)
Abstract. One of the cases of violence that never ends and the number of cases continues to increase is bullying. Not only done directly, bullying can also occur indirectly, such as being shunned by the environment because it is considered different. Basically, bullying is done repeatedly by the perpetrator until the victim feels physically and psychologically intimidated. As of February 2020, 2,473 cases of bullying have been recorded that have been reported to KPAI. One of the bad effects of bullying on victims is the psychological or mental impact of the victim. Those who experience bullying victims tend to close themselves. One way that they can open up is by communicating with the right people. Rangkoel Care is one of the foundations engaged in mental health and is quite professional in responding to victims of mental disorders, including victims of bullying, by communicating with Rangkoel Care, victims of bullying have a strong possibility to reopen themselves. The purpose of this study was to find out about experiences, motives and meanings when carrying out the communication process carried out by bullying victims with Rangkoel Care. Then, this study was compiled using a qualitative method with a phenomenological approach because researchers can find out more about the experiences of bullying victims during the self-disclosure communication process with the Rangkoel Care foundation. The results of the study show that (1) the experience of the victim when carrying out the communication process of self-disclosure is in accordance with Adler and Rodman's theory in which the stages of self-disclosure are clichés, facts, opinions, and feelings. (2) the meaning of conducting a self-disclosure process for victims of bullying equally interprets it as a positive thing and is considered important to do. (3) the motives of the victims of bullying in carrying out the communication process of self-disclosure, namely they do it purely from within and the desire of themselves. Abstrak. Pada dasarnya bullying dilakukan secara berulang-ulang oleh pelaku hingga korban merasa terintimidasi secara fisik dan psikologis. Hingga Februari 2020 sudah tercatat 2.473 kasus bullying yang dillaporkan pada KPAI. Dampak buruk dari bullying pada korban salah satunya pada piskologis atau mental korban. Mereka yang mengalami korban bullying cenderung akan menutup dirinya.Salah satu cara agar mereka dapat membuka diri yaitu dengan melakukan proses komunikasi dengan orang yang tepat. Rangkoel Care merupakan salah satu yayasan yang bergerak di bidang kesehatan mental dan cukup propesional dalam menanggapi korban yang mengalami gangguan mental termasuk korban bullying, dengan melakukan komunikasi bersama Rangkoel Care korban bullying besar kemungkinannya untuk membuka dirinya kembali. Tujuan dari penelitian ini adalah untuk mengetahui tentang pengalaman, motif dan makna ketika melakukan proses komunikasi yang dilakukan korban bullying dengan Rangkoel Care. Kemudian, penelitian ini disusun menggunakan metode kualitatif dengan pendekatan fenomenologi karena peneliti dapat mengetahui lebih dalam perihal pengalaman korban bullying selama melakukan proses komunikasi keterbukaan diri dengan yayasan Rangkoel Care. Hasil penelitian menunjukkan bahwa (1) pengalaman korban saat melaksanakan proses komunikasi keterbukaan diri sesuai dengan teori Adler dan Rodman yang di mana tahapan keterbukaan diri yaitu klise, fakta, opini, dan perasaan. (2) makna melakukan proses keterbukaan diri bagi korban bullying sama-sama memaknainya sebagai suatu hal yang positif dan dianggap penting untuk dilakukan. (3) motif korban bullying dalam melakukan proses komunikasi keterbukaan diri yaitu mereka melakukannya pure berasal dari dalam diri dan keinginan dari diri sendiri.